Methodological features of teaching general inorganic chemistry to students of the faculty of pharmacy - Fedotov, S. O.; Федотов, Сергій Олегович (Запорізький державний медичний університет, 2023)
General and inorganic chemistry is one of the most important subjects in the system of higher pharmaceutical education. It is the basis for studying medical and biological disciplines (biological chemistry, normal physiology, pathology, pharmacology), as well as special disciplines - pharmacognosy, pharmaceutical chemistry, toxicological chemistry, clinical pharmacy and drug technology. The purpose of this work is an attempt to highlight the teaching of general and inorganic chemistry at the Faculty of Pharmacy of ZSMU in the conditions of the credit-module system [1].